Impact of Antimicrobial Agents against Oral Isolates - Ali, Muna Jalal; Makky, Essam A.; M. M., Yusoff (2015)
Tooth decay is considered the most widespread infectious disease in the world. Its spread increases with time, and this increase is associated significantly with the change of dietary mode of modern humans. This study aims to isolate and identify the important bacteria related to tooth decay, determine the sensitivity of bacteria in certain types of antimicrobial agents, and study the effect of heavy metals on bacterial isolates. A total of 50 swabs were collected from the mouths of patients from both sexes, with ages ranging from 1–60 years. The patients were advised to consult with dental clinics and specialized centers to isolate and identify the causative agents associated with oral diseases. Results showed that infection rates in younger age groups (1–20 and 20–40) are higher than the elder group (40–60), with percent incidence of 44% and 32%, respectively. Antibiotic sensitivity test against the isolates showed that chloramphenicol had the highest sensitivity effect with 83.2% followed by rifampicin and gentamicin with 81.35%, penicillin G with 64.40%, and streptomycin with 16.94% Also, these differences were found have lower effect for isolates against (10) heavy metals, where it showed resistance to Iron 3.38% , then nickel , aluminum ,copper, lead to 20.33%, 22.03%, 27.11%, 28.81% respectively, also sliver shown 57.62%. And, this similarity were found have sensitive to antimony and chromium 61.01%. while appeared sensitivity to mercury and cadmium by 100, 86.44.